Development of Pencak Silat Sports Achievements in Grobogan Subdistrict in The Preparation of The 2023 PORPROV - Wulandari, Indah; Nurrachmad, Limpad (Department of Physical Education, Sport, Health and Recreation, 2024)
The acvhievement developmentis an importance factor to achieve sports performance optimally. The refore, the management of Pencak Silat sports in Grobogan Regency conduct achievement development in preparation for Porprov 2023. This study aims to determine the coaching of Pencak Silat achievements, challenges, and obstacles. This research uses descriptive qualitative methods with three research subjects, namely the IPSI management of Grobogan Regency. Data collection was obtained using observation, interview, and documentation techniques. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results showed that 1) Grobogan Regency’s Pencak Silat achievement coaching includes the Grobogan Regency’s coaching system through the 3 stages; Recruitment of athletes and coaches; facilities and infrastructure thatfulfill the predetermined standards, the role of the management and fund management from KONI which is passably. 2) The challenges and obstacles include athlete disciplinecaused of poor training, the relationship between the athletes, coaches, and management is not good. Research results show that achievement development of Grobogan Regency Pencak Silat in preparation for Porprov 2023 is in accordance AD-ART. However, there are several obstacles and challenges. Researchers suggest that monitor the development of each athlete thoroughly, and monitor the implementation of coaching directly and establish good relationships with athletes and coaches